2016
DOI: 10.1097/hjh.0000000000000859
|View full text |Cite
|
Sign up to set email alerts
|

Digital interventions to promote self-management in adults with hypertension systematic review and meta-analysis

Abstract: Objective:To synthesize the evidence for using interactive digital interventions (IDIs) to support patient self-management of hypertension, and to determine their impact on control and reduction of blood pressure.Method:Systematic review with meta-analysis was undertaken with a search performed in MEDLINE, EMBASE, CINAHL, PsycINFO, ERIC, Cochrane Library, DoPHER, TROPHI, Social Science Citation Index and Science Citation Index. The population was adults (>18 years) with hypertension, intervention was an IDI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 39 publications
8
104
0
1
Order By: Relevance
“…Notably, this result was in accordance with other studies using mobile and other similar older technologies [11,46]. In one metaanalysis, a decrease of 5 mm Hg in DBP or 10 mm Hg in SBP was found to reduce coronary heart disease events by 22% and stroke by 41% [47], as a decrease of 1 mm Hg in SBP leads to a 5% reduction in the risk of stroke [46]. The findings of this review are in line with other systematic reviews that involved smartphone and tablet based intervention in managing chronic diseases, which showed that the use of apps has the potential to improve health outcomes among those living with chronic diseases [8,10,11,49,50].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Notably, this result was in accordance with other studies using mobile and other similar older technologies [11,46]. In one metaanalysis, a decrease of 5 mm Hg in DBP or 10 mm Hg in SBP was found to reduce coronary heart disease events by 22% and stroke by 41% [47], as a decrease of 1 mm Hg in SBP leads to a 5% reduction in the risk of stroke [46]. The findings of this review are in line with other systematic reviews that involved smartphone and tablet based intervention in managing chronic diseases, which showed that the use of apps has the potential to improve health outcomes among those living with chronic diseases [8,10,11,49,50].…”
Section: Discussionsupporting
confidence: 93%
“…Notably, this result was in accordance with other studies using mobile and other similar older technologies [11,46]. In one metaanalysis, a decrease of 5 mm Hg in DBP or 10 mm Hg in SBP was found to reduce coronary heart disease events by 22% and stroke by 41% [47], as a decrease of 1 mm Hg in SBP leads to a 5% reduction in the risk of stroke [46].…”
Section: Discussionsupporting
confidence: 87%
“…A recent meta-analysis of interactive digital interventions demonstrated that interactive digital interventions are effective in lowering both SBP (weighted mean difference [WMD] −3.74 mm Hg, 95% confidence interval [CI] −5.28 to −2.19) and DBP (WMD −2.37 mm Hg, 95% CI −4.35 to −0.40) compared with usual care. 75 Few studies in the review included medication adherence as an outcome measure. Despite the promising results, little is known about the sustainability, long-term effectiveness, and active components of these interventions; thus, the evidence is not robust enough to warrant a policy or practice change at this time.…”
Section: New Frontiers In the Promotion Of Medication Adherencementioning
confidence: 99%
“…33 There is accumulating evidence that DIs can deliver better and more efficient healthcare in the context of hypertension, 34 35 confirmed by a recent systematic review and meta-analysis undertaken by our team. 36 Therefore, the HOME BP programme has been developed to incorporate previously identified effective intervention components (self-monitoring, preplanned medication titrations and behavioural support) delivered in an acceptable and feasible online format.…”
Section: A 10 MM Hgmentioning
confidence: 99%